2021
DOI: 10.34084/bshr.948974
|View full text |Cite
|
Sign up to set email alerts
|

Scopus Veri Tabanına Dayalı Bibliyometrik Değerlendirme: Miyelodisplastik Sendrom Konulu Yayınların Global Analizi ve Türkiye Kaynaklı Yayınların Değerlendirilmesi

Abstract: Amaç Miyelodisplastik sendromlar (MDS), klonal hematopoez, bir veya daha fazla sitopeni (anemi, nötropeni ve/veya trombositopeni) ve anormal hücresel olgunlaşma ile karakterize edilen bir grup hematolojik maligniteyi içerir. Bu hastalık grubu, yaş arttıkça insidansı artmakta ve hekimlerin bu konuda bilgi sahibi olması gerekmektedir. MDS hematoloji alanının ilgi çeken konu başlıklarındandır. Bibliyometrik değerlendirme ile ülkemiz ve dünyada bu konuda yapılan yayınların değerlendirildiği bu yazı, bu konuda çalı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…As mostly previously studies [11][12][13][14][15][16][17], our study showed that the majority of articles from USA. This may due to research findings and large number of researchers in USA.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…As mostly previously studies [11][12][13][14][15][16][17], our study showed that the majority of articles from USA. This may due to research findings and large number of researchers in USA.…”
Section: Discussionsupporting
confidence: 84%
“…Bibliometric analysis which is social science study area, has been started to use in medical area in recent years. As different researchers made this analysis on different medical topics, it became easier to give way to perspective for future studies [11][12][13][14][15][16]. Pubmed, The Web of Science (WOS) and Scopus databases are mostly common databases mainly preferred in bibliometric analyses [11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…research productivity. Gaps in study areas can be found and even comparisons of prior studies on a topic (Alkan Çeviker et al, 2021b;Durgun, 2021;Dindar Demiray et al, 2021a;Dindar Demiray et al, 2021b;Gürler et al, 2021;Köylüoğlu et al, 2021;Küçük et al, 2021;Özlü, 2021a;Özlü, 2021b;Mızrakçı, 2022;Akyüz et al ,2022). In bibliometric analysis, Internet databases are commonly used.…”
Section: Discussionmentioning
confidence: 99%
“…Sharing extremely early information with the public, researchers, government organizations, institutes, and at national and international levels is of considerable interest. Safety measures and guidelines are implemented based on this type of information [11][12][13][14][15][16][17][18][19][20] . A few bibliometric studies have been performed on research relating to rotavirus 19,20 , but no similar studies on rotavirus vaccine have been published yet.…”
Section: Discussionmentioning
confidence: 99%